Inosine Prevents Colorectal Cancer Progression by Inducing M1 Phenotypic Polarization of Macrophages - Yuchen Ma; Xiaoli Qian; Qun Yu; Yadan Dong; Jiapeng Wang; Heng Liu; Huai Xiao (Molecules)
Inosine (IS) is a naturally occurring metabolite of adenosine with potent immunomodulatory effects. This study investigates the immunomodulatory effects of inosine, particularly its ability to inhibit the development of colorectal cancer (CRC) cells CT26 through modulation of macrophage phenotypes. Aside from the already reported effects of inosine on T cells, in this study, in vitro experiments revealed that inosine could modulate macrophage phenotype. The effects of inosine on the M1/M2 macrophage polarization were investigated at the cellular level. Its role in regulating CRC proliferation and migration was further examined. In addition, a CT26 tumor mouse model was established to assess the mechanism of action of inosine by tumor weight measurement, immunohistochemistry, and immunofluorescence. Inosine significantly increased M1 macrophage markers CD86 and iNOS and enhanced the anti-tumor activity of M1 macrophages, effectively inhibiting CRC progression and metastasis potential. In vivo, inosine had significant tumor inhibitory activity. It also significantly reduced the expression of Ki-67 and promoted the polarization of M1 macrophages.